An analysis of interactional metadiscourse markers in political science research articles - Noor Afifah Nawawi,; Ting, Su-Hie (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study examined the interactional metadiscourse markers used in higher and lower tiered political science research articles. The specific aspects studied were: (1) the frequencies of five categories of interactional markers; and (2) the distribution of interactional markers by rhetorical section. The descriptive study which involved the analysis of political science research articles published in 40 SCOPUS-indexed journals (20 Quartile 1; 20 Quartiles 3 and 4) conducted using Hyland’s (2005) interpersonal metadiscourse model identified 10,903 markers. Both Q1 and Q3-Q4 political science articles have boosters and hedges as the most frequently used markers, and engagement markers as the least used marker. There are significant differences between the higher and lower tiered political science research articles in the frequencies of interactional metadiscourse markers found in rhetorical sections. The method section has the most self-mentions, particularly in articles published in Q1 journals. Writers of articles published in Q1 journals prioritise boosters, indicating confidence in emphasising certainty, but writers of articles published in Q3-Q4 journals prioritise hedges over boosters. The Q1 articles have more attitude markers in the introduction and resultsdiscussion- conclusion sections but less in the abstract and method sections, but writers of Q3- Q4 articles use attitude markers in similar frequencies across sections. The findings suggest that the nature of reader engagement varies with rhetorical section in research articles.